Grapiprant e dipirona na analgesia pós-operatória de gatas submetidas a ovariohisterectomia eletiva - Gasparotto, Jean Carlos (2022)
Grapiprant, a drug belonging to the new piprant class, is a potent antagonist with high specificity to the prostaglandin E2 EP4 receptor. It is currently approved in several countries for the control of chronic pain and inflammation in dogs. Although the literature still lacks studies evaluating its effectiveness in cats, it has been shown to be safe for administration to felines for long periods. Therefore, the objective of this study is to evaluate the efficacy of the administration of grapiprant associated with dipyrone for postoperative analgesia in cats undergoing elective ovariohysterectomy. For this, 26 adult cats were used, with no defined breed and considered healthy through clinical evaluation and complementary exams. After three days of adaptation to the environment and the team, the animals underwent elective ovariohysterectomy by celiotomy and were allocated into three groups according to the treatment used: DIP (Dipyrone Group, 25 mg.kg-1 8/8 hours), GRA ( Grapiprant Group, 2 mg.kg-1 24/24 hours) and GDG (Grapiprant Group 2 mg.kg-1 24/24 hours + dipyrone 25 mg.kg-1 8/8 hours). In both groups, the drugs were administered orally, starting 2 hours before surgery. Postoperative pain was assessed using the UNESP multidimensional scale for feline pain (EUNESP) and the Glasgow composite scale adapted for felines (EGLASGOW). Assessments were performed on the third day of adaptation (Baseline) and 1, 3, 6, 8, 12 and 24 hours after the surgical procedure. Blood and urine were collected for evaluation of blood count, serum biochemistry and urinalysis, immediately before the administration of treatments (Basal) and 24 hours after extubation. In the assessment of postoperative pain, pain scores differed over time between the three treatments. In all evaluated groups, the animals required a high analgesic rescue rate (GDG = 62.50%; DIP = 87.50% and GRA = 50.00%) in the first 3 hours of evaluation. The GDG and DIP groups had lower pain scores from 3 to 24 hours. Among the times for the same group, only GDG had lower pain scores at the twenty-fourth hour of evaluation when compared to the third hour. No animal in the study required analgesic rescue from the 6th hour of evaluation. The GDG obtained a significant increase in leukocytes from baseline to 24 hours. At baseline, the GRA group had higher albumin levels compared to the DIP group. At 24 hours, albumin in GRA was higher in relation to both GDG and DIP. Other parameters of hemoglobin, hematocrit, erythrocytes, platelets, alanine aminotransferase, aspartate aminotransferase, gammaglutamyltransferase, alkaline phosphatase, creatinine, urea, total plasma proteins, urinary pH and urinary protein/creatinine ratio did not differ between treatments. Despite being well tolerated, the results obtained by this study suggest that the administration of grapiprant and dipyrone, combined or alone, were not able to promote adequate immediate postoperative analgesia in cats undergoing elective ovariohysterectomy. No relevant hematological or biochemical changes were caused by any of the treatments in the first 24 hours evaluated.